Small two-bar specimen creep testing of Grade P91 steel at 650oC - Balhassn, S.M. Ali; Hyde, T.H.; Sun, Wei (De Gruyter, 2016)
Commonly used small creep specimen types, such as ring and impression creep specimens, are capable of providing minimum creep strain rate data from small volumes of material. However, these test types are unable to provide the creep rupture data. In this paper the recently developed two-bar specimen type, which can be used to obtain minimum creep strain rate and creep rupture creep data from small volumes of material, is described. Conversion relationships are used to convert (i) the applied load to the equivalent uniaxial stress, and (ii) the load line deformation rate to the equivalent uniaxial creep strain rate. The effects of the specimen dimension ratios on the conversion factors are also discussed in this paper. This paper also shows comparisons between two-bar specimen creep test data and the corresponding uniaxial creep test data, for grade P91 steel at 650°C.